Academic Education in the Context of its Accessibility for Blind Students - Bernadeta Szczupał (Lubelski Rocznik Pedagogiczny, 2022)
Introduction: Contemporary civilizational and cultural changes mean that blind students experience many psychological, social and physical challenges that can contribute to educational and social difficulties.